Conversão de furfural sobre zeólitas (Hf, Al)-ZSM-5 hierárquicas: controle da relação de sítios ácidos de Lewis e Brønsted e seu efeito na seletividade a produtos - Silva, Domingos Sérgio Araújo (Universidade Federal de São Carlos, 2021)
One-pot catalytic processes using heterogeneous acid catalysts have been a promising strategy for the valorization of platform molecules from lignocellulosic biomass, such as the transformation of furfural (Fur) to γ-valerolactone (GVL), levulinic acid (AL), levulinate esters, angelic lactones, etc., which can be used for the production of biofuels and additives, "green" solvents and chemical intermediates. Among the catalysts used in these processes, zeolites with Lewis acidity (L) and Brønsted (B) have demonstrated remarkable activities for coupling reactions by Meerwein Ponndorf-Verley transfer hydrogenation (MPV), hydrolysis/ alcoholysis and lactonization, which are routes of synthesis used in the conversion of molecules derived from lignocellulosic biomass. However, in the conversion of Fu, there are still limitations to be overcome, such as the development of more selective heterogeneous catalysts and with more active and accessible sites capable of performing the stages of hydrogenation by MPV and hydrolysis/alcoholysis. For MPV transfer hydrogenation reactions, zeolites with incorporated tetravalent metals (Ti, Sn, Zr, and Hf) have shown high activities, with those Hf-incorporated being the most active. In this context, this work proposes to develop hierarchical ZSM-5 zeolites containing L acid sites generated by Hf and B acid sites to be used as catalysts for the conversion of Fur in the presence of 2-propanol to more valuable products. For this purpose, hierarchical ZSM-5 zeolites with acidity of L and B were prepared by post-synthesis strategies of desilication, dealumination, and incorporation in liquid phase of Hf4+ cations. Analyses from XRD, DRS-UV-Vis, N2 physisorption, and FTIR in situ with adsorbed pyridine proved that the synthesis methods employed are capable to obtain micro-mesoporous ZSM-5 zeolites with both types of acid sites. In the catalytic tests, the hierarchical zeolites were able to catalyze the Fur conversion by in series reactions, generating mainly products such as GVL, AL, isopropyl levulinate (LI), β-angelic lactone (β AgL), and 2-(isopropoxymethyl)furan (2-IPF). The distribution of these products was strongly affected by the textural and acidic properties of the materials. The control of the B/L ratio proved to be essential in obtaining more efficient catalysts. To make this control, different strategies were used, such as heat treatments, changes in the degree of incorporation of the metallic cation, and physical mixtures of solids with L or B acidity. For the thermally treated mesoporous zeolites (Hf, Al)-ZSM-5, the selectivity to GVL decreased with the increase of the calcination temperature of the catalyst, and up to 450 °C its selectivity remained constant. The adjustment of the B/L ratio obtained with the change in the textural properties of the zeolite and subsequent insertion of Hf allowed changing the accessibility of the precursor of the metallic cation and its degree of incorporation, resulting in catalysts with different activities and selectivities. Physical mixtures of protonic hierarchical zeolites with HfO2 were also efficient for controlling the B/L ratio in a simpler and faster way. Using 30 mg of a micro-mesoporous zeolite (Hf, Al)-ZSM-5 containing 1.53 μmol of L and 4.14 μmol of B, it was possible to convert about 200 μmol of Fur after 40 h of reaction at 120 °C, obtaining GVL and LI yields of 35 and 23%, respectively. Catalytic tests varying the reaction conditions allowed to verify that the yields and selectivities to products of interest for the sectors of biofuels and chemical intermediates such as GVL and LI can be improved with the increase of the reaction temperature, catalyst mass and adjustment of the B/L ratio. In addition, catalyst reuse tests showed that the micro-mesoporous ZSM-5 zeolite having B and L sites generated by Hf maintained its catalytic activity until at least four consecutive reaction cycles. In general, the strategies presented were promising for the development of potential catalysts for the reactions of transformation of furan molecules into highly demanded products, such as biofuels, additives and chemical intermediates.
Furfural conversion over hierarchical (Hf, Al)-ZSM-5 zeolites: control of Lewis and Brønsted acid sites and their effect on selectivity to products
Keywords: Zeólita; ZSM-5; Sítios ácidos de Lewis e Brønsted; Catálise heterogênea; Conversão de furfural; Moléculas-plataforma; Biomassa lignocelulósica; Zeolite; Lewis and Brønsted acid sites; Heterogeneous catalysis; Furfural conversion; Platform molecules; Lignocellulosic biomass; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA